Effect of media and temperature on sporulation of Septoria apiicola, and of inoculum density on septoria blight severity in celery - Mudita, I.W.; Kushalappa, A.C. (Phytoprotection, 1991)
The number of conidia produced by Septoria apiicola was quantified on seven media incubated at 20°C. Conidia were produced abundantly on celery agar (CA) and celery potato dextrose agar (CPDA) after 12 days of incubation. In general, media containing celery decoction, including cleared V8 juice agar (CVA), produced more conidia than those without celery decoction. The number of conidia and the colony area produced per plate on CA increased with increase in temperature up to an optimum temperature and then decreased markedly. A second-order linear regression equation explained 99% of the variation in the number of conidia produced on CA plates incubated at temperatures ranging from 15 to 30°C, with the predicted optimum temperature of 22.4°C. Ninety eight percent of the variations in the colony area were explained by a linearized BETE-equation with the predicted optimal temperature of 22.7°C. Blight severity in celery (Apium graveolens var. dulce ) increased with increase in inoculum density. For inoculum density ranging from 5-140 conidia/cm2 of leaf surface, 92% of the variations in the number of lesions per leaf, pooled from two experiments, were explained by a second-order linear regression equation. The model was less reliable for inoculum densities less than 17 conidia/cm2 of leaf surface.